The effects of royal jelly on performance and fatty acid profles of different tissues in quail (Coturnix coturnix japonica) reared under high stocking density - Seven, Ismaıl; Şimşek, Ülkü Gülcihan; Gökçe, Zehra; Seven, Pınar Tatlı; Arslan, Aslıhan; Ökkeş,; Yilmaz, (My University, 2014)
To study the effects of royal jelly (RJ) on performance and fatty acid profles, 168 unsexed 8-day-old quails (Coturnix coturnixjaponica ) were assigned to 4 treatment groups. Groups were arranged as follows: control (LSD; 160 cm 2/quail and no supplementation),high stocking density (HSD; 80 cm 2/quail and no supplementation), HSD-RJ 250 [80 cm 2/quail and 250 mg/kg body weight (BW) RJgiven orally], and HSD-RJ 500 (80 cm 2/quail and 500 mg/kg BW RJ given orally). Body weight gain decreased signifcantly in the HSDgroup at day 42 (P < 0.01). Feed intake (FI) and feed conversion rate (FCR) were also signifcantly afected in the HSD group (P < 0.01).FI and FCR were improved by both doses of RJ. Both RJ doses increased total polyunsaturated fatty acid ratios in the breast, kidney (P< 0.001), leg, and liver (P < 0.05). Total saturated fatty acid ratios in leg (P < 0.01) and kidney (P < 0.05) tissues increased in the HSDgroup but decreased in the livers of HSD-RJ 250 group (P < 0.05). In conclusion, RJ supplementation improved performance parametersand unsaturated fatty acid ratios in the examined quail tissues.
Keywords: Biyoloji; Veterinerlik